GPIHBP1 Missense Mutations Often Cause Multimerization of GPIHBP1 and Thereby Prevent Lipoprotein Lipase Binding. Issue 4 (13th February 2015) - Beigneux, Anne P.; Fong, Loren G.; Bensadoun, André; Davies, Brandon S.J.; Oberer, Monika; Gårdsvoll, Henrik; Ploug, Michael; Young, Stephen G.
Abstract : Rationale: : GPIHBP1, a GPI-anchored protein of capillary endothelial cells, binds lipoprotein lipase (LPL) in the subendothelial spaces and shuttles it to the capillary lumen. GPIHBP1 missense mutations that interfere with LPL binding cause familial chylomicronemia. Objective: : We sought to understand mechanisms by which GPIHBP1 mutations prevent LPL binding and lead to chylomicronemia. Methods and Results: : We expressed mutant forms of GPIHBP1 in Chinese hamster ovary cells, rat and human endothelial cells, and Drosophila S2 cells. In each expression system, mutation of cysteines in GPIHBP1's Ly6 domain (including mutants identified in patients with chylomicronemia) led to the formation of disulfide-linked dimers and multimers. GPIHBP1 dimerization/multimerization was not unique to cysteine mutations; mutations in other amino acid residues, including several associated with chylomicronemia, also led to protein dimerization/multimerization. The loss of GPIHBP1 monomers is relevant to the pathogenesis of chylomicronemia because only GPIHBP1 monomers—and not dimers or multimers—are capable of binding LPL. One GPIHBP1 mutant, GPIHBP1-W109S, had distinctive properties. GPIHBP1-W109S lacked the ability to bind LPL but had a reduced propensity for forming dimers or multimers, suggesting that W109 might play a more direct role in binding LPL. In support of that idea, replacing W109 with any of 8 other amino acids abolished LPL binding—and often did so without promoting the formation of dimers and multimers. Conclusions: : Many amino acid substitutions in GPIHBP1's Ly6 domain that abolish LPL binding lead to protein dimerization/multimerization. Dimerization/multimerization is relevant to disease pathogenesis, given that only GPIHBP1 monomers are capable of binding LPL. Abstract : Supplemental Digital Content is available in the text.